Effect of Feeding Milk Replacer on Dry Matter Intake and Feed Efficiency in Holstein x Kankrej Crossbred Calves - Shukla, R.; Shah, S.V.; Pandya, P.R.; Lunagariya, P.M.; Pandya, S.S.; Divekar, B.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
An experiment was conducted on HF x Kankrej crossbred calves to study the effect of formulated milk replacer on nutrients intake, feed conversion efficiency, cost of feeding and disease incidence. Eighteen newly born calves of either sex were selected. The calves were fed colostrum up to 3 days and from 4th to 9th day whole milk at the rate of 12.5% of body weight. From 10th day the calves were randomly distributed in to three treatment group. The calves of T1 group received whole milk as per routine farm practice; T2 group was fed whole milk and commercial milk replacer as per manufacturer’s recommendation, whereas T3 group calves received formulated milk replacer @ 12.5 % of body weight with upper limit of 4 kg per day. The overall initial (day 10) and final (day 94) body weight of calves were 27.71±6.53 and 44.96±10.60 kg, respectively. Overall average dry matter intake (DMI) per day, as per cent body weight and per kg metabolic body weight (W0.75) was 0.52±0.02 kg, 1.45±0.03 kg and 35.34±0.78 g, respectively. The dry matter intake in T1 was significantly higher followed by T2 than T3. Overall intake of total digestible nutrients (TDN) on daily, per cent body weight and per kg W0.75 basis was 0.546±0.02 kg, 1.28±0.04 kg and 31.03±0.87 g, respectively. The DM intake for each kg gain was significantly lower in T3 (3.07 kg) and T1 (3.02) than T2 (4.79 kg) calves. The feed conversion efficiency (TDN intake kg/kg gain) was significantly superior in T3 (2.22) followed by T2 (4.23), whereas in T1 (2.95) it was intermediate. The feed cost and total rearing cost were lower (p
Keywords: Crossbred calves; Dry matter intake; Disease incidences; Feed conversion efficiency; Milk replacer; Economics